THE ROLE OF THE GENERAL PROLOGUE IN ESTABLISHING COMPOSITION - Suhrob Hasanov Shavkat ugli; So’poqova Mahfuza Furqat qizi; Shamsiddinov Bunyod (TADQIQOTLAR, 2026)
Annotation: This article examines the role of the General Prologue in establishing composition in Geoffrey Chaucer’s The Canterbury Tales. The General Prologue serves as the structural and thematic foundation of the entire work, introducing the setting, the pilgrimage framework, and the diverse group of characters who participate in the storytelling process. It plays a crucial role in shaping the narrative organization, connecting individual tales into a unified literary composition. Through vivid characterization, social representation, and detailed description, Chaucer creates a complex artistic structure that reflects the social, cultural, and moral realities of medieval England.